2019
DOI: 10.1111/ajpy.12215
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between psychoevolutionary fear of evaluation, cognitive distortions, and social anxiety symptoms: A preliminary structural equation model

Abstract: Social anxiety disorder is a mental health condition that affects 4.7% of Australians each year. The complex interplay between psychoevolutionary and cognitive models has become the focus of research in recent years, particularly with the development of the bivalent fear of evaluation model (i.e., negative and positive evaluation fears). The present study aimed to test a model of social anxiety symptoms using structural equation modelling, integrating previously fragmented evidence. A sample of 255 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Of the included data that were not meta-analyzed but added unique value to the narrative, the SAAS, which measures social anxiety symptoms related to appearance, found an additional 6.3% explained by BFOE, with FPE (6.3%), FNE (25.4%), and shared (20.8%) variance (Cook et al, 2020). The SPIN, which measures social anxiety symptoms related to appearance, had an additional 5.8% explained by BFOE, with FPE (5.9%), FNE (17.1%), and shared (6.9%) variance (Barber & Moscovitch, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included data that were not meta-analyzed but added unique value to the narrative, the SAAS, which measures social anxiety symptoms related to appearance, found an additional 6.3% explained by BFOE, with FPE (6.3%), FNE (25.4%), and shared (20.8%) variance (Cook et al, 2020). The SPIN, which measures social anxiety symptoms related to appearance, had an additional 5.8% explained by BFOE, with FPE (5.9%), FNE (17.1%), and shared (6.9%) variance (Barber & Moscovitch, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Reichenberger and Blechert (2018) concluded that FPE and FNE are distinct constructs. This finding is reflected in the literature both as cited by the review and more recently (Cook et al, 2020;Reichenberger et al, 2015;Weeks & Howell, 2012). A systematic review covering 33 articles identified from one database and scanning of reference lists undertaken by Fredrick and Luebbe (2020) also concluded that FPE and FNE are distinct constructs.…”
mentioning
confidence: 80%
“…The interpersonal relationships play a key role in wellbeing and mental health, and help in the self-actualization of individuals; therefore, it is important to identify the factors that disrupt these relationships [20]. Certain problems and crises can increase phobia in students.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…It should be kept in mind that in addition to those who are at risk of experiencing a severe case of the disease-older people and those with pre-existing medical conditions such as chronic respiratory disease, cardiovascular disease, and diabetes-other people also experience fear of COVID-19 ( Menotti, Puddu, Maiani, & Catasta, 2016 ). The most related biases to the fear of COVID-19 include fortune-telling, catastrophizing, fundamental attribution error, disqualifying positives, negative filter, overgeneralizing, dichotomous thinking, should statements, personalization, blaming, unfair comparisons, regret orientation, what if statements, emotional reasoning, ignoring counter-evidence, and judgment focus ( Ahorsu, Lin, Imani, Saffari, Griffiths, & Pakpour, 2020 ; Beck, Emery, & Greenberg, 2005 ; Cook, Meyer, & Knowles, 2019 ; Kuru, Safak, Özdemir, Tulacý, Özadel, Özkula, & Örsel, 2018 ; “List of cognitive biases”, 2020 ; Mann & Beech, 2003 ; Mizes, Landolf-Fritsche, & Grossman-McKee, 1987 ). On the other hand, several cognitive biases can relegate self-care practices.…”
mentioning
confidence: 99%
“…On the other hand, several cognitive biases can relegate self-care practices. These biases include optimism bias, ostrich effect, normalcy bias, apocalyptic beliefs, just-world hypothesis, accepting the victim role, and escaping responsibilities ( Ahorsu et al, 2020 ; Beck et al, 2005 ; Cook et al, 2019 ; Kuru et al, 2018 ; “List of cognitive biases”, 2020 ; Mann & Beech, 2003 ; Mizes et al, 1987 ).…”
mentioning
confidence: 99%